Microscopically observations for Rhodotorula sp biodegradation to crude and exhausted oil - El-Sharif , Thureia A.; Amnina, Fathia I. (المؤتمر العلمي الثاني لعلوم البيئة، 2015م, 2015)
In this present study Benghazi Lake or 23rd  of July Lake is considered as the major environmental and ecological problematic as results of several contaminations. A Success isolated of Rhodotorula strain from Benghazi Lake by three tested media of solid and broth, it cultivated for 2-4 weeks. The results are shown that it has highly degradable of crude oil and their derivatives reached about of 70-80 % during 1-2 weeks, while it has degraded to exhausted fuel oil of 95% for 7-10 days. The observations of two media 1, and 2 had visibility differences, whereas  the examination by light Microscope were closed similarity, due to the structure of slimy capsulated; it may be enhanced to the production of biosurfactant. A solubility test is confirmed that the ball shaped formation of medium 2 has structured of viscosity and biogases.  So this study has shown that a novel strain of Rhodotorula sp is promising to use in the bioremediation for the degradation of petroleum, their derivatives and exhausted fuel oil.
Keywords: Rhodotorula sp; biodegradation; crude and exhausted oil